STRATEGI KOMUNIKASI DIGITAL DIAN WIDAYANTI DALAM PEMBUATAN KONTEN HALAL DI INSTAGRAM: STRATEGI KOMUNIKASI DIGITAL DIAN WIDAYANTI DALAM PEMBUATAN KONTEN HALAL DI INSTAGRAM - Aprilia Permatasari, S.Kom. I, M.Ikom (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2025)
Dian Widayanti (@dianwidayanti) is an influencer who focuses on halal education through content on Instagram. Her Instagram account, created in 2011 and verified in 2023, initially contained personal activities but then transformed into a platform to educate the public about halal food and products. Dian actively shares content about halal food, containing critical information regarding halal certification and how to choose appropriate food. Through digital communication strategies, Dian has successfully built rapport with her audience and increased trust through educational content. This research used qualitative descriptive methods, including interviews with Dian, her creative team, and her followers. With over 128,000 followers, Dian has collaborated with numerous companies to market halal products. The content creation process includes ideation, production, editing, scheduling, and evaluation, involving partnerships with various brands. Dian is committed to providing accurate and relevant information about halal certification, including critical points in food, and educating her followers on choosing halal products, which has resulted in increased public awareness of halal consumption in Indonesia.